2020
DOI: 10.3390/ani10050907
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Content of Different Wheat and Maize Varieties and Their Impact on Metabolizable Energy Content and Nitrogen Utilization by Broilers

Abstract: The study aimed to determine the effect of nutrients of wheat (nine cultivars) and maize (nine cultivars) grain on nitrogen balance and apparent metabolizable energy (AMEN) content for broiler chickens. In vivo digestibility and balance trials were carried out with 90 Ross 308 chickens (2 × 9 groups with 5 birds per group) aged from 42 to 49 days, separately for each cultivar. Considerable variation within each cereal species in fiber and non-fiber carbohydrate fractions and nutrient digestibility of grain wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…Based on chemical analyses, the W-6 sample appeared to be of better quality than others, with high TAA content. Generally, the chemical properties of the samples were within the range previously reported for wheat ( Lasek et al., 2020 ; Lu et al., 2020 ).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Based on chemical analyses, the W-6 sample appeared to be of better quality than others, with high TAA content. Generally, the chemical properties of the samples were within the range previously reported for wheat ( Lasek et al., 2020 ; Lu et al., 2020 ).…”
Section: Discussionsupporting
confidence: 80%
“…This indicated that the wheat samples were representative. Different properties of wheat can be attributed to the growing environments ( Lasek et al., 2020 ), variety ( Azhar et al., 2019 ), and so on. Based on chemical analyses, the W-6 sample appeared to be of better quality than others, with high TAA content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It cannot be excluded that the enzyme supplement led to the absence of fiber effect. Hence, the inclusion of CF, ADF, and other fiber content into equations may improve the efficiency and accuracy of NE prediction [ 35 ]. Also, we compared the NE value measured by experiment (2,3) and NE predicted based on different equation as shown in Figure 1 and 2 which indicated that the regression equations generated in our study were relatively accurate.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the nutritional value of corn is critical for feed mills using corn of different origins throughout the year due to changes in suppliers caused by shifts in seasonality and price. In this context, the formulation of diets using average nutritional values assumes consistency among corn batches [ 11 , 22 ], and could impact broiler performance and processing yield. Therefore, understanding the influence of origin on corn nutritional variability is necessary for poultry nutritionists to formulate diets more precisely [ 23 ] and meet performance objectives.…”
Section: Introductionmentioning
confidence: 99%